2016
DOI: 10.1039/c5ra18146a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different metal oxides on the catalytic activity of γ-Al2O3–MgO supported bifunctional heterogeneous catalyst in biodiesel production from WCO

Abstract: The catalytic activity of different γ-Al2O3–MgO supported bifunctional solid catalysts was successfully evaluated by carrying out simultaneous esterification–transesterification in waste cooking oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Thus the transesterification reaction kinetics was calculated only for the forward reactions. Similar approach was applied in the literature during the biodiesel production kinetic study with different catalysts and feedstocks …”
Section: Resultssupporting
confidence: 88%
“…Thus the transesterification reaction kinetics was calculated only for the forward reactions. Similar approach was applied in the literature during the biodiesel production kinetic study with different catalysts and feedstocks …”
Section: Resultssupporting
confidence: 88%
“…These results indicated that the amounts of basicity and acidity on the catalyst surface could be the most important role in producing FAME at a relatively mild reaction condition. The highest FAME percentage yield can be obtained with the optimum number of active components available on the catalyst surface for one-pot esterication-transesterication reaction suggested by Farooq et al 18 From the above characterization and catalytic testing, PKSAC-K 2 CO 3(30%) CuO (5%) was chosen for further investigation by varying the wt% of K 2 CO 3 with 5 wt% of CuO.…”
Section: Catalyst Characterization For Screeningmentioning
confidence: 99%
“…The decreasing of basic active sites led to exposure of acid active components on the catalyst surface, thus affecting the amount of NH 3 desorption to slightly increase at the high temperature, as presented. 18 The comparison was also conducted for FTIR spectrum between the fresh catalyst and spent PKSAC-K 2 CO 3(30%) CuO (5%) catalyst aer the sixth reaction cycle. From Fig.…”
Section: Effect Of Reaction Durationmentioning
confidence: 99%
“…On the contrary, heterogeneous catalysts offer better alternative to their counterparts due to their ease of separation from the reaction medium [13,14]. In addition, heterogeneous catalysts are less expensive, are easily available, possess longer durability, are easy to regenerate, and are more stable at high temperatures and pressure [15].…”
Section: Introductionmentioning
confidence: 99%